Organs to Cells and Cells to Organoids: The Evolution of in vitro Central Nervous System Modelling - Pacitti, Dario; Privolizzi, Riccardo; Bax, Bridget E. (Frontiers in Cellular Neuroscience, 2019)
With one hundred billion neurons and one hundred trillion synapses, the human brain is not just the most complex organ in the human body, but has also been described as “the most complex thing in the universe”. The limited availability of human living brain tissue for the study of neurogenesis, neural processes and neurological disorders has resulted in more than a century-long strive from researchers worldwide to model the central nervous system (CNS) and dissect both its striking physiology and enigmatic pathophysiology. The invaluable knowledge gained with the use of animal models and post mortem human tissue remains limited to cross-species similarities and structural features, respectively. The advent of human induced pluripotent stem cell (hiPSC) and 3-D organoid technologies has revolutionised the approach to the study of human brain and CNS in vitro, presenting great potential for translational adoption in drug screening and regenerative medicine. We have surveyed more than one hundred years of research in CNS modelling and provide in this review an historical excursus of its evolution, from early neural tissue explants and organotypic cultures, to 2-D patient-derived cell monolayers, to the latest development of 3-D cerebral organoids. We have generated a comprehensive summary of CNS modelling techniques and approaches, protocol refinements throughout the course of decades and developments in the study of specific neuropathologies. Current limitations and caveats such as clonal variation, developmental stage, validation of pluripotency and chromosomal stability, functional assessment, reproducibility, accuracy and scalability of these models are also discussed.